2020
DOI: 10.7759/cureus.11091
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perception of Telemedicine in a Large Urban Inner-City Emergency Department: A Cross-Sectional Survey

Abstract: Introduction Telemedicine has the potential to ease emergency department (ED) overcrowding, improve ED throughput, and decrease the cost of medical care. Much of the current knowledge of telemedicine systems focuses on bringing more specialty care to the ED or improving access in rural areas. Limited research exists on patients' perception of telemedicine in an urban ED. Methods A survey exploring perceptions of telemedicine encounters was distributed to both providers and patients following mirrored encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The higher proportion of telemedicine users who have less than 4.5 million Rupiah as their monthly income (which is below Jakarta's regional minimum wage) may be attributed to its lower prices than regular care, thus becoming more economically accessible for those in the lower socioeconomic group (Sechrist et al, 2020). Another study also reports that, unlike traditional care, telemedicine allows the working population to get medical consultations without being absent from work or having to commute (Powell et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The higher proportion of telemedicine users who have less than 4.5 million Rupiah as their monthly income (which is below Jakarta's regional minimum wage) may be attributed to its lower prices than regular care, thus becoming more economically accessible for those in the lower socioeconomic group (Sechrist et al, 2020). Another study also reports that, unlike traditional care, telemedicine allows the working population to get medical consultations without being absent from work or having to commute (Powell et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Paediatric and young patients found to embrace telemedicine readily because they are using the latest technologies in their routine life. Interestingly, in our collected data, we saw the largest patient group engaged were patients above 51 years of age [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the video element, to a virtual clinic, has the ability to pick up non-verbal communication, making the video consultation effective as face-to-face (F2F) consultations. Negative influences include patient suitability and preference, and the lack of physical examination or ability to deliver a procedure or intervention [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine may provide a potential solution to the low-intensity medical care needs of many communities, particularly those in low socioeconomic communities, with the advent of prevalent smartphone availability, fast and widely available internet access, and pressing needs for healthcare services [10]. The benefits of reducing geographical constraints between patients and clinicians are also being leveraged to promote access to high-level critical care in places that are otherwise neglected by medical services [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study done with both providers and patients concluded that telemedicine may be a viable answer to limited medical care needs, given widespread access to cell phones with internet access and increasing demand for quality healthcare [23].…”
Section: Introductionmentioning
confidence: 99%